Tinjauan kebijakan penyediaan kawasan hutan untuk pembangunan food estate - Rahutomo, Andreas Budi; Alexander, M. Ikbal; Yustika, M, Miranda; Nurzirwa, Rizaldy Yudhista (Jurnal Bisnis Kehutanan dan Lingkungan, 2023)
The problem of food security in Indonesia has become an endless polemic from the era of President Soekarno's regime until now; providing food for all Indonesian people has still experienced many obstacles. Indonesia still needs help from other countries to meet people's basic needs by importing food from neighboring countries, such as rice imports from Thailand and soybeans, sugar, and garlic imported from foreign countries. Indonesia, as an agricultural country that should have a good level of food security, is still far from sufficient to meet food needs in its own country; this is what encourages the government to implement regulations that are expected to increase the level of food supply. The government has carried out various projects to answer challenges that continue to this day, from the Mega Rice Project in the Soeharto era to the formation of the Me-rauke Integrated Food and Energy Estate (MIFEE). In 2015, a 500,000-hectare food estate in Kalimantan was announced. In 2020, the issue of food security rose to the surface again due to the Covid-19 pandemic. This article explores the historical study of food estate discourse carried out by the government. It compares it with a critical review of the concept of food in Indonesia, the implementation of food estates, and food security from a literature review.